A multidimensional profile model of ambidexterity and innovation: an empirical case study. (2016) - Gottberg, Julian Von; Matheus, Thomas; Sarma, Meera
The purpose of this study is to examine which combination of dimensional features of ambidexterity influences innovation. Furthermore, this study examines the way in which the combination of dimensional features of ambidexterity influences an organisation's ability to innovate. We used a single holistic case study design and conducted semi-structured interviews with innovation experts from an outdoor company. We used template analysis to analyse our data. Unlike existing studies that examined ambidexterity in relation to innovation by offering theoretical arguments, simulations and little empirical research, we contribute a multidimensional profile model, comprised of a combination of the different features associated with the dimensions of organisational ambidexterity, to the existing literature. Based on this, we explain how some dimensional features of ambidexterity are identified, and subsequently how their combinations influence an organisation's ability to innovate. We also contribute to the literature on profile models of multidimensional constructs. We suggest that future research could longitudinally examine organisational ambidexterity from a multidimensional view through multiple cross-industry cases.